2020
DOI: 10.3389/fimmu.2020.00231
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone H3K27 Acetylation Orchestrates Interleukin-9-Mediated and Plays an Anti-Inflammatory Role in Cisplatin-Induced Acute Kidney Injury

Abstract: Nephrotoxicity is a major side effect of cisplatin (CP)-and platinum-related chemotherapy, and inflammation contributes to disease pathogenesis. Interleukin-9 (IL-9) is a pleiotropic cytokine associated with inflammation. Here, we investigated the key role of IL-9 as a regulator of protective mechanisms in CP-induced acute kidney injury (AKI). We observed that IL-9 was decreased not only in a CP-induced AKI mouse model but also in THP-1 and RAW264.7 cell lines. Seventy-two hours post-CP injection, renal dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In AKI induced by I/R, a metabolic reprogramming also has been reported with a glycolytic shift and PDC inhibition [ 29 ], indicating a decreased activity of this enzyme complex and ergo a reduction in acetyl-CoA synthesis; moreover, in AKI induced by cisplatin, H3K27 acetylation is reduced, and the restoration of its acetylation levels decreases kidney damage [ 30 , 31 ]. Hence, in CKD and AKI, there appears to be a decrease in acetyl-CoA levels, which in turn impacts histone acetylation.…”
Section: Acetyl-coamentioning
confidence: 99%
“…In AKI induced by I/R, a metabolic reprogramming also has been reported with a glycolytic shift and PDC inhibition [ 29 ], indicating a decreased activity of this enzyme complex and ergo a reduction in acetyl-CoA synthesis; moreover, in AKI induced by cisplatin, H3K27 acetylation is reduced, and the restoration of its acetylation levels decreases kidney damage [ 30 , 31 ]. Hence, in CKD and AKI, there appears to be a decrease in acetyl-CoA levels, which in turn impacts histone acetylation.…”
Section: Acetyl-coamentioning
confidence: 99%
“…HDACs are subdivided into four types: class I (HDAC1, 2, 3, and 8), class IIa (HDAC4, 5, 7, and 9), class IIb (HDAC6 and 10), class III (SIRT1-7), and class IV (HDAC11) [ 58 ]. One of the strategies to decrease CDDP-induced nephrotoxicity has been the use of HDACs class II inhibitors, as their overexpression is associated with increased apoptosis [ 62 , 63 ]. Studies have reported that the level of acetylated histone H3 is modified after CDDP treatment, but CDDP does not alter the abundance of histone H4 [ 64 ].…”
Section: Cisplatin Nephrotoxicity and Histone Modificationsmentioning
confidence: 99%
“…Finally, reduction of HDAC4 and HDAC5 with LMK-235 blocks the caspase-3 cleavage in HRCE cells [ 66 ]. The use of TSA, valproate (VPA) or suberoylanilide hydroxamic acid (SAHA) can confer kidney protection during CDDP treatment by H3K27 acetylation and IL-9 down-regulation [ 62 ], increase of BMP-7 [ 63 ], AMWAP [ 68 , 69 ] and PSTPIP2 [ 70 ]; increased CREB phosphorylation [ 71 ], reduction of caspase-3 activation [ 71 ] or by autophagy stimulation [ 72 ]. Even more, it has been demonstrated that SAHA inhibits and TSA delays phosphorylation, acetylation, and activation of p53 in rat proximal tubular cells [ 67 ].…”
Section: Cisplatin Nephrotoxicity and Histone Modificationsmentioning
confidence: 99%
“…The TLR-4/NF-kB signaling pathway is one of the most important signaling pathways in regulating various downstream inflammatory factors and participate in the regulation of inflammatory responses (Tian et al, 2019). Excessive secretion of pro-inflammatory cytokines is associated with exacerbated kidney injury (Jiang et al, 2020). It is clear that HIF-1α regulates VEGF protein synthesis through the PI3K pathway and the hypoxia-activated PI3K/Akt/mTOR pathway (Park et al, 2015).…”
Section: Inflammatory Reactionmentioning
confidence: 99%